PENGARUH JUMLAH BIBIT PADA BERBAGAI SISTEM TAJARWO TERHADAP PENINGKATAN PRODUKTIVITAS PADI (ORYZA SATIVA L.) (THE INFLUENCE OF SEEDS AMOUNT ON VARIOUS OF TAJARWO SYSTEM TO PADDY PRODUCTIVITY INCREASING) - Suharno, Suharno; Ariani, Koeswini Tri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2013)
The study was conducted in rice fields, Sengir Farmers Group, Sumberharjo Village, BP3K working area, Prambanan Subdistrict, Sleman, Yogyakarta. The specification of land, cropping Rice - Rice - Rice harvest index (IP 300). The study was conducted during the dry season from July - November 2012 (known as Srondolan Rice). The research aimed to determine the effect of cropping treatment tajarwo system to increase rice productivity, determine the effect of treatment the number of seeds per planting hole to increase rice productivity, and the interaction between cropping systems combined treatment with the number of seeds per planting hole to increase the productivity of rice (Oryza sativa L).The research used Randomized Complete Block Design Experiment with 2 factors: the number of seedlings planted per hole (B) and legowo planting system (L). Each with 3 levels, (B2, B4, and B6) for the for B factor, and (L1, L2, and L3) to L factor. There was increasing on rice productivity to 1.58 tonnes / hectare.Treatment of the number of seeds per hole did not give significantly affect to productivity of dry milled per hectare (t/ha). There was increasing of productivity to 0.29 tonnes / hectare by